2013
DOI: 10.1371/journal.pone.0072021
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Monoclonal Antibody Delivery in Oncology: The Example of Bevacizumab

Abstract: Developing therapeutic monoclonal antibodies paves the way for new strategies in oncology using targeted therapy which should improve specificity. However, due to a lack of biomarkers, a personalized therapy scheme cannot always be applied with monoclonal antibodies. As a consequence, the efficacy or side effects associated with this type of treatment often appear to be sporadic. Bevacizumab is a therapeutic monoclonal antibody targeting Vascular Endothelial Growth Factor (VEGF). It is used to limit tumor vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…It has been previously reported that lower trough bevacizumab concentrations are associated with poorer clinical outcomes . However, our study for the first time has identified three distinct groups of subpopulations within patients with mCRC, where bevacizumab exposure is directly and positively related to OS.…”
Section: Discussionmentioning
confidence: 54%
“…It has been previously reported that lower trough bevacizumab concentrations are associated with poorer clinical outcomes . However, our study for the first time has identified three distinct groups of subpopulations within patients with mCRC, where bevacizumab exposure is directly and positively related to OS.…”
Section: Discussionmentioning
confidence: 54%
“…This is consistent with the known half-life (~19 days) and previously published PK data [ 28 ]. Average blood concentration of bevacizumab has indeed been described to be 88 mg/L after the first dose [ 29 ]. These data are very close to ours (median of 111 mg/L after one or two cycles) suggesting the robustness of our results.…”
Section: Discussionmentioning
confidence: 99%
“…Low serum bevacizumab concentrations were associated with a lack of efficacy, while high concentrations were associated with side effects. Thus, they concluded that serum bevacizumab concentration appears to be a useful clinical pharmacodynamic marker [ 74 ]. In 2016 two other groups published their results regarding the role of bevacizumab plasma concentrations.…”
Section: Bevacizumab Levels-therapeutic Drug Monitoring (Tdm)mentioning
confidence: 99%